The transmembrane protein Crumbs displays complex dynamics during follicular morphogenesis and is regulated competitively by Moesin and aPKC - Sherrard, Kristin M. (Development, 2015)
The transmembrane protein Crumbs (Crb) functions in apical polarity and epithelial integrity. To better understand its role in epithelial morphogenesis, we examined Crb localization and dynamics in the late follicular epithelium of Drosophila. Crb was unexpectedly dynamic during middle-to-late stages of egg chamber development, being lost from the marginal zone (MZ) in stage 9 before abruptly returning at the end of stage 10b, then undergoing a pulse of endocytosis in stage 12. The reappearance of MZ Crb is necessary to maintain an intact adherens junction and MZ. Although Crb has been proposed to interact through its juxtamembrane domain with Moesin (Moe), a FERM domain protein that regulates the cortical actin cytoskeleton, the functional significance of this interaction is poorly understood. We found that whereas the Crb juxtamembrane domain was not required for adherens junction integrity, it was necessary for MZ localization of Moe, aPKC and F-actin. Furthermore, Moe and aPKC functioned antagonistically, suggesting that Moe limits Crb levels by reducing its interactions with the apical Par network. Additionally, Moe mutant cells lost Crb from the apical membrane and accumulated excess Crb at the MZ, suggesting that Moe regulates Crb distribution at the membrane. Together, these studies reveal reciprocal interactions between Crb, Moe and aPKC during cellular morphogenesis.